Մի ճշգրտում Ձիրավի դաշտի մասին - Եղիազարյան, Վանո; Գրիգորյան, Արա (Արմավ հրատ.)
The scientific novelty of the article lies in the addition and correction of the information about the Dzirav plain stated in the «Dictionary of Toponyms of Surrounding Regions of Armenia». The Dzirav plain is located not at the northern foot of Mount Npat, as erroneously stated in the dictionary, but on the eastern side of Mount Npat, which has been proved by bibliographic data and other facts of Armenian studies. Научной новизной статьи является дополнение и разъяснение информации о Дзиравском поле, которая приводится в «Словаре топонимов Армении и прилегающих областей». Дзиравское поле находится не у северных подножий горной вершины Нпат, как по ошибке представлено в указанном словаре, а в восточной части горы Нпат, что было обосновано библиографическими данными и фактами, имеющимися в других арменоведческих исследованиях.
Keywords: Բանասիրություն